Concentration Of The baculovirus Autographa californica M nucleopolyhedrovirus (AcMNPV) by ultrafiltration - Michalsky, Ronald; Passarelli, A. Lorena; Pfromm, Peter H.; Czermak, Peter (My University, 2010)
Concentration and retention of a rod-shaped virus during tangential flow ultrafiltration (UF) was assessed to evaluate the potential of membrane-based downstream methods with advantages such as easy scale-up for industrial processes. A recombinant baculovirus of the non-spherical Autographa californica M nucleopolyhedrovirus (AcMNPV), vHSGFP, expressing egfp was filtered using polyethersulfone membranes ranging from 30 to 1000 kDa molecular weight cut-off (MWCO). A 20-fold virus concentration was achieved when a membrane cut-off range of 100 to 1000 kDa was tested. Fouling was observed and cake formation and pore plugging were postulated as concurrent causes with different impact depending on the MWCO. A reduction of virus concentration in the range of 2 to 5 log units in the permeate was observed illustrating the potential of membrane-based virus filtration as a useful unit operation in downstream processing.
Keywords: Autographa californica M nucleopolyhedrovirus; Membrane filtration; Virus concentration; Downstream processing